1986
DOI: 10.1007/bf03028035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead on Na+,K+ ATPase activity in the developing brain of intra-uterine growth-retarded rats

Abstract: Lead (Pb) intoxication in developing mammals, including humans, produces serious brain damage. In addition, it is known that nutritional status influences the susceptibility to Pb toxicity. We developed an in utero undernutrition model based on restriction of blood supply to fetuses on d 17 of pregnancy (IUGR rats). The aim of this study was to investigate in vitro the possible effect of Pb on Na+, K+ATPase activity in the brain of developing IUGR and control rats from 6 to 60 d after birth. In addition, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We recently observed that Pb potently inhibited the activity of mitochondrial complex-I (NADH-ubiquinone reductase), the enzyme that is critical to the energy production in mitochondrial respiratory chain (unpublished data). Others have reported that Pb inhibits cellular ATPases (Chanez et al, 1986;Rajanna et al, 1991). In addition, we have demonstrated that Pb exposure promotes the translocation of protein kinase C (PKC) from the cytosol to membrane in the choroid plexus .…”
Section: Discussionmentioning
confidence: 99%
“…We recently observed that Pb potently inhibited the activity of mitochondrial complex-I (NADH-ubiquinone reductase), the enzyme that is critical to the energy production in mitochondrial respiratory chain (unpublished data). Others have reported that Pb inhibits cellular ATPases (Chanez et al, 1986;Rajanna et al, 1991). In addition, we have demonstrated that Pb exposure promotes the translocation of protein kinase C (PKC) from the cytosol to membrane in the choroid plexus .…”
Section: Discussionmentioning
confidence: 99%
“…Axonal excitability studies were undertaken during the acute phase and in convalescence to assess whether lead exerts its neurotoxic effects through dysfunction of axonal biophysical properties, a hypothesis that has received support from in vitro studies 5. The patient gave informed consent to the procedures, which were approved by institutional ethics committees.…”
Section: Methodsmentioning
confidence: 99%